Shear strength, avalanches, and structures of soft cohesive particles under shear - Saitoh, Kuniyasu (Frontiers in Physics, 2025)
The physics of granular materials, including rheology and jamming, is strongly influenced by cohesive forces between the constituent grains. Despite significant progress in understanding the mechanical properties of granular materials, it remains unresolved how the range and strength of cohesive interactions influence mechanical failure or avalanches. In this study, we use molecular dynamics simulations to investigate simple shear flows of soft cohesive particles. The particles are coated with thin sticky layers, and both the range and strength of cohesive interactions are determined by the layer thickness. We examine shear strength, force chains, particle displacements, and avalanches, and find that these quantities change drastically even when the thickness of the sticky layers is only 1% of the particle diameter. We also analyze avalanche statistics and find that the avalanche size, maximum stress drop rate, and dimensionless avalanche duration are related by scaling laws. Remarkably, the scaling exponents of the scaling laws are independent of the layer thickness but differ from the predictions of mean-field theory. Furthermore, the power-law exponents for the avalanche size distribution and the distribution of the dimensionless avalanche duration are universal but do not agree with mean-field predictions. We confirm that the exponents estimated from numerical data are mutually consistent. In addition, we show that particle displacements at mechanical failure tend to be localized when the cohesive forces are sufficiently strong.